Efek Kompres Hangat dan Pemberian Air Kelapa terhadap Dismenore Primer pada Remaja Putri Pondok Pesantren Modern Al Ikhlash Putri Kuningan: The Effects of Warm Compress and Coconut Water Administration on the Primary Dysmenorrhea in Teenage Girls of the Al Ikhlash Putri Modern Boarding School, Kuningan Regency - Rukoyah, Oya Siti; Triwahyuningsih, Ria Yulianti; Kumalasary, Diyanah; Nurfita, Nisa Rizki (Universitas Airlangga, 2024)
Background: The menstruating teenage girls show a high primary dysmenorrhea incidence which is very discomforting, in form of abdominal cramps or pain spread to the back, headache, nausea and vomiting, as well as diarrhea, so they have to take a rest in a certain period of time and stop carrying out their activities and works. Objectives: This research aims to identify the effects of warm compress and coconut water administration towards the primary dysmenorrhea in teenage girls of Al-Ikhlash Putri Modern Boarding School, Kuningan Regency. Methods: This research was the pre-experimental research with one group pretest-posttest design. Total 83 teenage girls from classes 1 to 3 in Senior High School at the age of 14-18 years were selected as population. Instrument used was the Standard Operating Procedure (SOP) and the checklist sheet (observation and interview). Data processing was carried out using the SPSS program. The purposive sampling was applied in taking the sample, so 26 teenagers, relevant to the inclusion and exclusion criteria, were obtained. Data collected were primary data. Univariate and bivariate analyses were utilized with the paired t-test in testing effects and chi-square test in testing correlation of every variable. Results: There was a difference test with p-value 0.000, while the significant effect was found in menstrual pain before and after warm compress and coconut water administration in teenage girls. Conclusions: Warm compress and regularly consuming coconut water can minimize the menstrual pain in teenage girls.